2006
DOI: 10.2174/157340606777724013
|View full text |Cite
|
Sign up to set email alerts
|

The Structure - Antituberculosis Activity Relationships Study in a Series of 5-(4-Aminophenyl)-4-Substituted-2,4-Dihydro-3h-1,2,4-Triazole-3-Thione Derivatives. A Combined Electronic-Topological and Neural Networks Approach

Abstract: Antituberculosis activity of several 5-(4-aminophenyl)-4-alkyl/aryl-2,4-dihydro-3H-1,2,4-triazole-3-thiones (1-9) and their thiourea derivatives (10-31) were screened for their antimycobacterial activities against Mycobacterium tuberculosis H37Rv using the BACTEC 460 radiometric system. Of the synthesized compounds, 10-12, 30 were the most active derivatives exhibiting more than 90 % inhibition of mycobacterial growth at 12.5 microg/mL. Structure-activity relationships study was performed for the given series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…As well as thiourea based compounds, new candidates bearing both heterocycles and thiourea moieties have been shown as promising antituberculosis agents. 7,8,10,16) It is known that heterocyclic scaffolds possess a leading role in designing novel class of chemotypes as drug candidates. Among them, 1,3,4-thiadiazoles have been reported to possess a wide range of biological activities including antiproliferative, antibacterial, antifungal, and antimycobacterial functions.…”
mentioning
confidence: 99%
“…As well as thiourea based compounds, new candidates bearing both heterocycles and thiourea moieties have been shown as promising antituberculosis agents. 7,8,10,16) It is known that heterocyclic scaffolds possess a leading role in designing novel class of chemotypes as drug candidates. Among them, 1,3,4-thiadiazoles have been reported to possess a wide range of biological activities including antiproliferative, antibacterial, antifungal, and antimycobacterial functions.…”
mentioning
confidence: 99%
“…However, the procedure of the activity prediction is difficult enough and needs the expert's participation. To make the procedure easier and faster, the ETM application was followed by the ANNs application, and, as a whole, the calculations were named the combined ETM-ANNs approach [4,15].…”
Section: Brief Description Of the Etm-annsmentioning
confidence: 99%
“…The value of k was found by varying it in the range of [1, N mol ]. The researches have shown that the values of k that are higher than 2 practically do not improve the quality of the models obtained [5,15]. The SOM of Kohonen realizes a nonlinear projection of high-dimensional data set onto a low-dimensional domain.…”
Section: )mentioning
confidence: 99%
“…In this regard, it has been established that heterocyclic compounds play an important role in designing new class of structural entities for medicinal applications . Among pharmacologically important heterocyclic compounds, 1,2,4‐triazole and its derivatives are attracted considerable attention due to their interesting biological activities . These azoles exert their antitubercular activity through inhibition of cytochrome P450 gene CYP121 (CYP121) by a mechanism in which the heterocyclic nitrogen (N‐3 of imidazole or N‐4 of 1,2,4‐triazole) binds to the sixth co‐ordination site of the heme iron atom of the porphyrin in the substrate‐binding site of the enzyme .…”
Section: Introductionmentioning
confidence: 99%